Temozolomide treatment of pituitary carcinomas and atypical adenomas: systematic review of case reports - Ji, Yan (Neurooncol Pract, 2016)
BACKGROUND: Pituitary carcinomas (PC) and atypical pituitary adenomas (APA) are rare variants of pituitary tumors for which no evidence-based treatment currently exists. We sought to determine whether temozolomide represents an effective chemotherapeutic option for patients with PC and APA. METHODS: A systematic review was performed using all published cases of PC and APA treated with temozolomide, and for which information on treatment regimen, clinical response, and survival could be identified. The primary goal of this analysis was to describe overall survival and progression-free survival among PC and APA patients after temozolomide treatment. Secondary goals included assessment of response rate and biomarkers of response. RESULTS: We identified 57 cases and obtained follow-up data on 54 patients (31 APA and 23 PC) for analysis. Estimates of 5-year progression-free survival and overall survival were 21.9% and 57.4% for patients with APA and 36.1% and 56.2% for patients with PC. Among those who responded to temozolomide, overall survival was marginally statistically significantly greater for patients on long-term temozolomide therapy compared with those who were not (5-year overall survival 91.7% vs 54.1%, P = .08); Progression-free survival results were similar but not statistically significant. The objective response rate was 48.4% for patients with APA and 65.2% for patients with PC. Stable disease occurred in 29% of APA and 17.4% of PC patients. Neither histology nor expression of Ki-67 correlated with response; however, negative O(6)-methylguanine-DNA methyltransferase staining was strongly related to response to temozolomide in patients with APA (P < .001). CONCLUSIONS: Temozolomide is an effective treatment of both PC and APA, and long-term treatment can be considered for particularly aggressive cases.